The closure of derivative average radial integrable spaces in the Bloch space - Xiangling Zhu; Rong Yang (Journal of Inequalities and Applications)
Abstract A description of the closure in the Bloch space of the Bloch functions that are in the derivative average radial integrable space is given. As a byproduct, we get some new characterizations for the Bloch space B $\mathcal{B}$ , the little Bloch space B 0 $\mathcal{B}_{0}$ , and the closure of the space H 2 ∩ B $H^{2}\cap \mathcal{B}$ in the Bloch norm.